Organizational studies in brazilian context: new directions of knowledge or epistemic dependence? : New directions of knowledge or epistemic dependence? ("Revista Gestión y Conexiones", 2023)
Organizational studies incorporate the political, socioeconomic and historical-cultural transformations of a nation. In Brazilian context, such research brought greater autonomy through the work of Alberto Guerreiro Ramos and Maurício Tragtenberg, precursors of the onto-epistemological construction prior to the Anglo-Saxon criticism based on mainstream of administration. The objective of the study was to understand the evolution of organizational studies in Brazilian context. For this, a systematic review of the literature was used to map the studies that bring a legitimate idea for a national theorization. The relevance of national researchers and the influence of their studies in Latin America and in the world contributed to a disentangling of dominant theories. Finally, the national constructs allowed a dialogue with the theme, and bequeathed pluriverse lenses in the analysis of discourses and contexts that keep organizational studies in evidence.